Modifications of Liquid Electrolyte for Monolithic Dye-sensitized Solar Cells - Putri Nur Anggraini; Erlyta Septa Rosa; Natalita Maulani Nursam; Rico Fernado Sinaga; Shobih Shobih (Jurnal Elektronika dan Telekomunikasi, 2021)
Dye-sensitized solar cells (DSSC) has been well known as a highly competitive photovoltaic technology owing to its interesting characteristics, such as, low-cost, simple, and convenient to modify both chemically and physically. One way to reduce the production cost of DSSCs is to conduct a structural modification in the form of a monolithic structure by using a single conductive substrate to accommodate both photoelectrode and counter electrode. However, the photovoltaic performance of monolithic DSSCs is typically still lacking compared to its conventional DSSCs counterparts that uses sandwich structure. One of the crucial factors that determine the photovoltaic performance of a monolithic DSSC is its electrolyte. In this work, the performance of monolithic DSSCs were studied through modifications of the electrolyte component. Two types of commercial liquid electrolytes that have different chemical properties were used and combined into various compositions, and the resulting DSSCs performances were compared. The stability of the monolithic cells was also monitored by measuring the cells repeatedly under the same condition. The result showed that during the first measurement the highest performance with a power conversion efficiency of 1.69% was achieved by the cell with a higher viscosity electrolyte. Meanwhile, the most stable performance is shown by the cell containing lower viscosity electrolyte, which achieved an efficiency of 0.66% that measured on day 35.